Position and enforcement practice of the People's Republic of China's pharmaceutical data exclusivity protection - Li N; Yu X; Pecht M (Dove Medical Press, 2016)
Na Li,1 Xiang Yu,2 Michael Pecht3 1School of Law, Ningbo University, Ningbo, People’s Republic of China; 2School of Law and Politics, Ningbo Institute of Technology, Zhejiang University, Ningbo, People’s Republic of China; 3Center for Advanced Life Cycle Engineering, University of Maryland, College Park, MD, USAAbstract: The concept of pharmaceutical data exclusivity protection comes from the West. The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) establishes the basic rules for pharmaceutical data exclusivity protection. People’s Republic of China’s domestic law is consistent with the TRIPS agreement. In the drug registration approval process of the People’s Republic of China’s Drug Supervision Department, pharmaceutical data exclusivity protection has encountered some problems, including data authentication, exclusive rights to data, number of drugs requiring data to be submitted, and drug costs. In view of the long-term interests of the People’s Republic of China’s pharmaceutical industry and intellectual property protection trends, there are a lot of difficulties in the enforcement of pharmaceutical data exclusivity protection law that need to be overcome. Some measures can be taken, such as establishing a shorter data exclusivity protection period, only protecting the data submitted and relied on in the People’s Republic of China, only protecting the drugs that use new chemical components, allowing application and necessary research before the expiry of pharmaceutical data exclusivity protection period of generic drugs.Keywords: drug, developing countries, approval, competition